Beyond Profit: The Role of CSR in Enhancing Corporate Reputation - Aripin, Norhani; Hussin, Muhammad Rosni Amir; Amran, Noor Afza; Ahmad, Halimah Nasibah; Ahmad, Mohd Shahfari (Indian Journal of Information Sources and Services, 2025)
In response to the COVID-19 pandemic, corporations worldwide faced challenges balancing profit-driven objectives with social responsibilities. This study was conducted to understand CSR activities initiated by Telekom Malaysia (TM), specifically by TM Kedah/Perlis during the COVID-19 pandemic and the benefit of the activities. This study also aimed to understand the impact of the initiatives on their reputation. A qualitative method was employed to develop a deeper understanding of participants’ views and by observation, interpretation, or generalisation of the CSR initiatives. This case study adopted multiple data collection methods, including semi-structured interviews with TM’s employees and their recipients, field observation and document analysis. In conclusion, the food bank initiative undertaken by TM Kedah/Perlis during the COVID-19 pandemic yielded various benefits to several parties, i.e., the B40 recipients, the grocery shop owners, and TM itself. The testimonials and insights shared by the recipients and TM Kedah/Perlis representatives have evidenced the positive impact of this initiative on various stakeholders.